Hip Arthroscopy Failure in the Setting of Acetabular Dysplasia: A Concerning Trend?. Issue 7 (21st July 2017) - Clohisy, John C.; An, Tonya; Haynes, Jacob; Nepple, Jeffrey J.; Schoenecker, Perry; Baca, Geneva; ,
Objectives: Despite the success of hip arthroscopy, evidence suggests that arthroscopy alone is inadequate for treatment of conditions such as acetabular dysplasia (AD) due to its failure to correct structural deformity. Our objective was to define the incidence of failed hip arthroscopy in patients with symptomatic AD requiring periacetabular osteotomy (PAO). We secondarily analyzed the patient and structural characteristics of the failed arthroscopy cases. Methods: Utilizing a prospective, multicenter joint preservation database, we identified a cohort of primary AD patients from 2009-2014 who underwent PAO after a single prior ipsilateral hip arthroscopy. A comparison cohort of PAO patients without prior arthroscopy was isolated. Patients with hip disease attributable to cerebral palsy, Perthes, etc. were excluded. Demographic and radiographic data were summarized for each category. We compared the proportion of PAO after failed hip arthroscopy between the beginning and end of the study period by 2-tailed z-test with P<0.05 regarded as statistically significant. Results: Ninety-nine patients (99 hips) had received arthroscopic surgery prior to PAO, while 1053 patients (1103 hips) underwent PAO without prior hip arthroscopy. The proportion of PAO procedures after previous ipsilateral hip surgery stayed constant (13-19%); however, the incidence of PAO after previous hip arthroscopy increased from 2.5% in 2009 to 9.8% in 2014 (P=0.004). Over the 6 year period, the rate of all PAO procedures increased 12% per year, whereas rates of PAO after hip arthroscopy grew an average 54% per year. Female sex, increased average LCEA and ACEA, and decreased acetabular inclination were associated with failed hip arthroscopy (P<0.01). Conclusion: Over the last six years, we have seen clear increases in the rate of PAO after previous hip arthroscopy. Though the rate of PAO following previous ipsilateral surgery remains constant, hip arthroscopies now constitute almost 60% of those previous surgery attempts. Additionally, we have identified mild dysplastic features and female sex as characteristics that are associated with failure of hip arthroscopy. These results are consistent with prior literature suggesting that inadequately corrected structural deformity is the most common indication for revision surgery. These findings raise concern that isolated hip arthroscopy is being increasingly utilized in patients with acetabular dysplasia and highlight the need for refined surgical indications for hip arthroscopy and further investigation into its impact on subsequent surgeries. Figure 1 Rate of ipsilateral periacetabular osteotomy (PAO) procedures petformed after any previous surgery and after hip arthroscopy (HS)